2009
DOI: 10.1016/j.tifs.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Fish gelatin: a renewable material for developing active biodegradable films

Abstract: Most films used to preserve foodstuffs are made from synthetic plastic materials.However, for environmental reasons, attention has recently turned to biodegradable films. Gelatin has been extensively studied for its film forming capacity and applicability as an outer covering to protect food against drying, light, and oxygen. Moreover, it is 5 one of the first materials proposed as a carrier of bioactive components. Gelatins from alternatives to mammalian species are gaining prominence, especially gelatins fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
215
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(229 citation statements)
references
References 107 publications
(117 reference statements)
5
215
0
9
Order By: Relevance
“…It has been widely used both in food and pharmaceutical industry due to its excellent functional properties. It has been reported that the annual growth rate of gelatin production in the past seven years was about 3-4 % (Gómez-Guillén et al 2009). At present, mammalian gelatins, such as pig and cow gelatin are most widely used in the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used both in food and pharmaceutical industry due to its excellent functional properties. It has been reported that the annual growth rate of gelatin production in the past seven years was about 3-4 % (Gómez-Guillén et al 2009). At present, mammalian gelatins, such as pig and cow gelatin are most widely used in the world.…”
Section: Introductionmentioning
confidence: 99%
“…At present, mammalian gelatins, such as pig and cow gelatin are most widely used in the world. It had been reported that the worldwide production of gelatin was 326,000 t, with gelatin extraction of pig skin (46 %), bovine hide (29.4 %), pork and cattle bones (23.1 %) and other sources (1.5 %) (Gómez-Guillén et al 2009). However, it is significant to explore new resource for gelatin due to some health-related and social-culture problems.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous studies, this is true in the case of cold-water fish species, such as cod, salmon and alaska pollock. However, researchers have pointed out that gelatin from tropical and subtropical warm-water fish species (tilapia, Nile perch, catfish) might have similar physicochemical properties to that of mammalian, depending on the species, type of raw material and processing conditions (Gilsenan and Ross-Murphy 2000;Gómez-Guillén et al 2009;Jamilah and Harvinder 2002;Muyonga et al 2004;Rawdkuen et al 2010) Research on fish gelatin is important for the development of methods to produce gelatin from fish processing as replacements for mammalian sources. Scale of production and quality of gelatin depend on extraction method (Montero and Gómez-Guillén 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several protein-based polymers are already thoroughly explored and among them, gelatine represents one of the most intensively used worldwide with an increasing demand [3]. Gelatine is easily available, transparent, flexible and resilient, rendering a preferred base material vastly used by food, pharmaceutical, cosmetic and several specialized industries [4,5].…”
Section: Introductionmentioning
confidence: 99%